Predictors of pain reduction following manual therapy in patients with temporomandibular disorders: a protocol for a prospective observational study - Alison B Rushton; Nicola R Heneghan; Deborah Falla; Giacomo Asquini; Andrea Edoardo Bianchi; Giulia Borromeo; Matteo Locatelli (BMJ Open)
Introduction Temporomandibular disorders (TMDs) are principally characterised by pain in the craniomandibular area and probable limitations of jaw opening. Manual therapy, like other recommended conservative treatments included in clinical guidelines, is commonly used to treat patients with TMD to reduce pain and improve function. However, outcomes may be variable. The aim of this study is to identify predictors associated with pain reduction in patients with TMD following manual therapy by analysing a combination of patient-reported outcome measures and clinical tests. Such knowledge will support a more personalised management approach by facilitating clinical decision-making.Methods/analysis An observational prospective design will recruit a cohort of 100 adults with a diagnosis of TMD (according to Axis I of the Diagnostic Criteria for TMD) at a Dental Hospital in Italy. Patients will be treated with four weekly sessions of manual therapy applied to craniomandibular structures. An array of predictors has been chosen based on previous research on prognostic factors for TMD and altered pain modulation in musculoskeletal disorders. Candidate predictors including demographic variables, general health variables, psychosocial features, TMD characteristics and clinical tests of the temporomandibular joint and masticatory muscles will be collected at baseline. Definition of good outcome is a clinically significant reduction of pain intensity over the last week (≥30% reduction Visual Analogue Scale) immediately following the four week intervention. Exploratory factor analysis will be applied to analyse factor loading of candidate predictors for good outcome at four weeks. Subsequently, a logistic multivariable regression model will be performed to calculate low and high risk of good outcome.Ethics and dissemination Ethical approval has been obtained from the ‘Fondazione IRCCS Ca’ Granda Ospedale Maggiore Policlinico’ and University of Birmingham Ethics Committee. The results will be submitted for publication in a peer-reviewed journal and presented at conferences.Trial registration number NCT03990662; Pre-results.